Stakeholder feedback on The CARD™ System to improve the vaccination experience at school. (29th March 2019) - Taddio, Anna; Freedman, Tamlyn; Wong, Horace; McMurtry, C Meghan; MacDonald, Noni; Ilersich, Anthony N T; Ilersich, Angelo L T; McDowall, Tori
Abstract: Objective: School-based vaccination programs can be a source of distress for many students due to the pain from the needle injection and related fears. We created a multifaceted Knowledge Translation (KT) intervention to address vaccination and pain, fear, and fainting called The CARD™ System. The objectives were to document acceptability of key tools included in the multifaceted KT intervention and their effectiveness in improving knowledge and attitudes about vaccination pain and fear. Methods: Quantitative and qualitative methods were used. Students, school staff, public health nurses, and parents participated in separate focus groups whereby they independently completed a knowledge and attitudes survey and provided structured and qualitative feedback on key KT tools of the multifaceted KT intervention. They then repeated the knowledge and attitudes survey. Results: Altogether, 22 students (grade 6 and 7), 16 school staff (principals, grade 7 and 8 teachers, resource teachers, secretaries), 10 nurses (injecting, charge, and school nurses), and 3 parents participated. Knowledge test scores increased post-KT tool review: 8.5 (2.1) versus 7.3 (1.9); P<0.001. Attitudes were more positive about the individual nature of pain and fear experience during vaccination. Student fear scores were lower post-tool review: 5.1 (2.9) versus 4.6 (3.0); P<0.001. The majority of the participants reported they understood all the information, the amount was just right and that the information was useful. Discussion: The KT tools were demonstrated to be acceptable and to improve knowledge. Future research is warranted to determine their impact on student experience during school vaccinations.